(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Phenology has been studied in 20 species of shrubby species of Rosaceae in Livoberezhne Polissia. The main phenological phases are prolonged with higher effective temperature; the data on particular phases are shown. Investigated plants have highly adaptive abilities and may be recommended for wide use in Northern Ukraine.